UPAYA MENINGKATKAN KEMAPUAN MENULIS RECOUNT DALAM BAHASA INGGRIS MELALUI PENILAIAN PORTOFOLIO SISWA KELAS VIIID MTsN PITALAH KABUPATEN TANAH DATAR - Zulmaida, Zulmaida (STKIP Pesisir Selatan, 2019)
Based on the ability to write class VIII.D MTsN Pitalah in Sub-English Language Subjects Reveal the meaning in functional written text and simple short monologue in the form of narrative and recount to interact with the surrounding environment it was found that the ability to write students in English subjects is still low. The average ability to write students is still under the KKM. The purpose of this study was to describe and obtain information about efforts to increase the ability to write students in English subjects through a Portfolio learning model in Class VIII.D MTsN, Tanah Datar District. This research is a classroom action research. The research procedures in this study include planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 28 students of Class VIII.D MTsN Pitalah. Research data was collected using observation sheets and daily tests. Data were analyzed using percentages. Based on the results of the research and discussion that have been stated, it can be concluded that the Portfolio learning model can increase the ability to write students in English subjects at MTsN Pitalah. The ability to write students from cycle I to cycle II. The ability to write students in the first cycle is 59.62 (Less), increasing to 83.82 (good) with an increase of 24.21.